Risk Phenotypes, Comorbidities, Pharmacotherapy, and Electroconvulsive Therapy (ECT) in a Cohort with Difficult-to-Treat Depression in Comparison to an Unmedicated Control Group - Maier, Hannah B.; Borchert, Anton; Neyazi, Alexandra; Moschny, Nicole; Schülke, Rasmus; Bundies, Gabriel L.; Folsche, Thorsten; Gaspert, Anastasia; Seifert, Johanna; Bleich, Stefan; Scherf-Clavel, Maike; Unterecker, Stefan; Deckert, Jürgen; Frieling, Helge; Weber, Heike (Pharmacopsychiatry, 2024)
Background Approximately 15–25% of depressed patients suffer from difficult-to-treat depression (DTD). Patients with DTD require a thorough examination to avoid the oversight of treatable (psychiatric/somatic) comorbidities or (pseudo-)resistance to antidepressant drugs (ADs). Polymorphisms of the cytochrome P450 (CYP) enzymes 2D6 and 2C19, which play a major role in the metabolism of ADs, may contribute to resistance to ADs. Patients with DTD might benefit from electroconvulsive therapy (ECT).Methods We enrolled 109 patients with DTD and 29 untreated depressed controls (UDC). We assessed risk phenotypes, comorbidities, and treatment, including ECT. We also performed pharmacokinetic analyses of CYP2D6 and CYP2C19.Results DTD patients significantly more often suffered from comorbid psychiatric diseases, especially ICD-10: F40-F48 (DTD:40.4%, UDC:17.2%, OR 11.87, p=0.011) than UDC patients. DTD patients receiving ECT were more likely to achieve remission (37.7% vs. 11.8%, OR=3.96, p=0.023). Treatment with ADs did not differ between remitters and non-remitters. No significant differences were observed in the distribution of CYP2D6 and CYP2C19 variants between both groups.Conclusion Patients with DTD appear to experience comorbid neurotic stress and somatoform disorders (ICD-10: F40 – F48) more frequently. Therefore, a comprehensive differential diagnosis is crucial when patients do not respond sufficiently to antidepressant medication. Genotyping CYP2D6 and CYP2C19 should be considered.
Keywords: difficult-to-treat-depression; phenotyping; CYP enzymes; psychiatric comorbidities; pharmacogenetics; ECT